Purinergic Cooperation Between P2Y2 and P2X7 Receptors Promote Cutaneous Leishmaniasis Control: Involvement of Pannexin-1 and Leukotrienes - Thorstenberg, Maria Luiza; Rangel Ferreira, Marcos Vinícius; Amorim, Natália; Canetti, Claudio; Morrone, Fernanda B.; Alves Filho, José Carlos; Coutinho-Silva, Robson (Frontiers in Immunology, 2018)
The release of damage-associated molecular patterns (DAMPs), including UTP and ATP to the extracellular milieu is a key component of innate immune response to infection. Previously, we showed that macrophage infection by the protozoan parasite Leishmania amazonensis – the etiological agent of cutaneous leishmaniasis – can be controlled by ATP- and UTP-mediated activation of P2Y and P2X7 receptors (activated by UTP/ATP and ATP, respectively), which provided comparable immune responses against the parasite. Interestingly, in context of L. amazonensis infection UTP/P2Y triggered apoptosis, reactive oxygen species (ROS) and oxide nitric (NO) production, which are characteristic of P2X7 receptor activation. Here, we examined a possible “cross-talk” between P2Y2 and P2X7 receptors, and the requirement for pannexin-1 (PANX-1) in the control of L. amazonensis infection in mouse peritoneal macrophages and in vivo. UTP treatment reduced L. amazonensis parasite load, induced extracellular ATP release (which was pannexin-1 (PANX-1) dependent), and triggered leukotriene B4 (LTB4) production in macrophages. UTP-induced parasite control was blocked by pharmacological antagonism of P2Y2 or P2X7 receptors, and was absent in macrophages lacking P2X7 or PANX-1. In addition, ATP release induced by UTP was also inhibited by PANX-1 blocker carbenoxolone (CBX), and partially reversed by inhibitors of vesicle traffic and actin cytoskeleton dynamics. In vivo, UTP treatment reduced footpad and popliteal lymph node parasite load, and the lesion in wild type (WT) mice; fact not observed in P2X7-/- mice. Our data reveal that P2Y2 and P2X7 receptors cooperate to trigger potent innate immune responses against L. amazonensis infection.